Songkabala Tradition in the Makassarese Society: Local Values and Messages of the Al-Qur’an an Anthropological Perspective on Islamic Law - Sohrah, Sohrah; Husna, Asmaul; Akbar, Rahmatul; Sugirman, Andi; Arfah, M. Thahir (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
Local traditions as religious practices in Indonesian society experience dialectic and integration of Islamic teachings. Every ethnicity in Indonesia has socio-cultural mechanisms in dealing with calamities and disasters which are influenced by religion and customs. This then dialectic with the practice of Islamic law. The study seeks to examine songkabala, a tradition of mutual acceptance in the Makassarese society. These traditions are local values that contain Al-Qur’anic teachings. This is an empirical legal study employing an anthropological perspective on Islamic law. In-depth interviews and literature reviews focused on three districts inhabited by Makassarese, namely Maros, Gowa, and Takalar, were employed to collect data. The study indicates that songkabala is the spirit of Al-Qur’anic verses associated to human responses to calamity, including remembrance of Allah, gratitude, and ritualized prayer. Songkabala is a Makassarese folk tradition that contains Al-Qur’anic themes. The verses of the Al-Qur’an indicate that the command to pray and the remembrance of Allah are incorporated into the songkabala ritual. Consequently, there is no incompatibility between the songkabala tradition and the teachings of the Al-Qur’an.